Answer:
1)· 5x + 2y = 9. First we solve for y. 2y= 9 -5x. y=(9-5x)/2. Now that we have the value of y. We substitute on the original equation and resolve. 5x + 2y = 95x + 2y = 9 5x + 2(9-5x)/2 = 9 5x + 9 - 5x = 9 9 = 9
That would be x = 1
Now substitute and resolve to find y.
5(1) + 2y = 9
5 + 2y = 9
2y = 4
y = 2
So our answer x=1 and y = 2. (1,2)
Proof :
5(1) + 2(2) = 9
5+ 4 = 9
9 = 9
Step-by-step explanation:
hoped it helped for the first one i didnt now the second one
We need Pythagoras theorem here
a^2+b^2 = c^2
a, b = legs of a right-triangle
c = length of hypotenuse
Let S=shorter leg, in cm, then longer leg=S+2 cm
use Pythagoras theorem
S^2+(S+2)^2 = (10 cm)^2
expand (S+2)^2
S^2 + S^2+4S+4 = 100 cm^2 [collect terms and isolate]
2S^2+4S = 100-4 = 96 cm^2
simplify and form standard form of quadratic
S^2+2S-48=0
Solve by factoring
(S+8)(S-6) = 0 means (S+8)=0, S=-8
or (S-6)=0, S=6
Reject nengative root, so
Shorter leg = 6 cm
Longer leg = 6+2 cm = 8 cm
Hypotenuse (given) = 10 cm
Twenty-two of the players said that they preferred that the games be played on Saturdays. Ivan correctly determined that the margin of error, E, of his survey using a 99% confidence interval (z*score 2.58) is approximately 18%
Ivan surveyed 49 randomly select
5 miles high is one of the sides of a triangle depending on accuracy level
h^2=x^2+y^2
we don't have 2 distances
Tan A=O/a
O=a tan A
We solve for O because the angle is at the top of the line going up and we want the opposite angle that is along the ground
O=5×tan(173.7/2)=90.854033512
The distance he can see is:
90.85*2~181.7 miles
Now we need to find the distance between lines:
The north south distance between each line is 69 miles
thus the number of degrees he will see will be:
181.7/69
=2 19/30
Standard form (which I assume is what they want you to turn these into) is y=mx+b.
12x-5y=20 is y=2.4x-4.
Subtract 12x from both sides, -5y=-12x+20.
Multiply both sides by -1, 5y=12x-20.
Divide both sides by 5, y=2.4x-4.
y=x+4 is already in standard form- I'm not quite sure what to do.
3x+y=3 is y=-3x+3.
Subtract 3x from both sides, y=-3x+3.
x=-y+3 is y=-x+3
Ad y to both sides, y+x=3.
Subtract x from both sides, y=-x+3.